Reimagining antibody-dependent cellular cytotoxicity in cancer: the potential of natural killer cell engagers. Issue 11 (November 2022) - Pinto, Sheena; Pahl, Jens; Schottelius, Arndt; Carter, Paul J.; Koch, Joachim
Highlights: Antibody-dependent cellular cytotoxicity (ADCC) has been implicated as an important mechanism in several highly effective monoclonal antibody-mediated cancer therapies. Bi-, tri- and multispecific natural killer (NK) cell engagers have been designed to enhance and prolong NK cell-mediated responses by targeting different activating NK cell receptors. Monotherapy with NK cell engagers or adoptive NK cell transfer has shown efficacy and can be well tolerated in certain hematological and solid malignancies. NK cell engagers have the potential to complement therapeutics that enhance adaptive T cell responses. Innate cell engagers that are precomplexed with NK cells harbor potential as novel cryopreserved off-the-shelf candidate therapeutics with chimeric antigen receptor (CAR)-NK cell-like properties, capable of effective depletion of tumor cells. Significance: Novel antibody-engineering approaches are being utilized to maximize the potential of innate immune cells via antibody-dependent cellular cytotoxicity and might provide favorable clinical outcomes across various cancer types. Abstract: Bi-, tri- and multispecific antibodies have enabled the development of targeted cancer immunotherapies redirecting immune effector cells to eliminate malignantly transformed cells. These antibodies allow for simultaneous binding of surface antigens on malignant cells and activating receptors on innate immune cells, such as natural killer (NK) cells, macrophages, and neutrophils. Significant progress with such antibodies has been achieved, particularly in hematological malignancies. Nevertheless, several major challenges remain, including increasing their immunotherapeutic efficacy in a greater proportion of patients, particularly in those harboring solid tumors, and overcoming dose-limiting toxicities and immunogenicity. Here, we discuss novel antibody-engineering developments designed to maximize the potential of NK cells by NK cell engagers mediating antibody-dependent cellular cytotoxicity (ADCC), thereby expanding the armamentarium for cancer immunotherapy.